Balance hídrico e hidrológico de la cuenca media del río Gállego - Marín Jaime, José María (Geographicalia, 2017)
Sited in the Pyrenees slope, the Gallego river is one of the most important tributaries of the right bank of the Ebro basin. The hydrologica balance of the Middle Basin of this river is analysed, with the same methodology used in a precious study in the Upper-Basin, published in this magazine, showing the most significant differences between this two stretch of the Basin and their relationship with physical characteristics in both environments.